Emotional Prosody Recognition in Autism Spectrum Disorder Without Intellectual Disability: A Systematic Review and Meta-Analysis. - Luo, Qiyun; Zeng, Xiaoyan; Chen, Fei; Kuang, Chen (Journal of Autism & Developmental Disorders, 2026)
Emotional prosody recognition is vital for social interaction and has become a key focus in autism research. However, findings regarding emotional prosody recognition in individuals with autism spectrum disorder without intellectual disability (ASD-without-ID) remain inconsistent. This study aims to address this inconsistency through a systematic review and meta-analysis, exploring potential factors that may account for the inconsistent results. A search across four major electronic databases identified 29 eligible studies comparing emotional prosody recognition in ASD-without-ID and typically developing (TD) participants. We identified several participant- and methodology-related moderators across these studies. Using a random-effects model, we found a moderate-to-large pooled effect (Hedges' g = − 0.65) for emotional prosody recognition in ASD-without-ID participants, which remained stable after adjusting for publication bias through the trim-and-fill method. Emotional complexity and participant age significantly moderated the heterogeneity of effect sizes across studies. The results indicate moderate differences in the recognition of basic emotions through prosody between individuals with ASD-without-ID and TD individuals, with more pronounced differences for complex emotions. The findings emphasize the distinct developmental trajectories of ASD-without-ID individuals. We highlight the need for further investigation into the underlying factors and mechanisms affecting emotional prosody recognition in this population, including meta-analyses examining the moderate effects of various IQ measures and studies involving speakers of tonal languages.